TNFα and IL-10 Expression in Dental Pulp after Administration of Gouramy Bone Paste (Osphronemus gouramy) and Calcium Hidroxide - Sunana Ageng Hikmawati; Dheamira Rosida; I Dewa Ayu Ratna Dewanti; Erawati Wulandari (Alliance oh Health Activists (AloHA), 2020)
Mechanical trauma causes pulp exposure and make the invasion of pathogenic microorganisms into the dental tissue. This condition causes pulp inflammation characterized by the release of pro-inflammatory cytokine tumor necrosis factor-α (TNF-α) and anti-inflammatory cytokine interleukin-10 (IL-10). Gouramy bone paste (Osphronemus gouramy) contains amino acids, omega-3, omega-6, and flavonoids which is thought to accelerate healing of inflamed pulp tissue that triggers decreased TNF-α expression and increased IL-10 expression. This study aims to analyze the expression of TNF-α and IL-10 in dental pulp after administration of Gouramy bone paste (Osphronemus gouramy) and calcium hydroxide. The sample size consisted of 24 Rattus novergicus which were divided into 3 groups i.e (K1) without the application of direct pulp capping material, (K2) with the application of calcium hydroxide, and (K3) with the application of gouramy bone paste. Data measured are the number of inflammatory cells (neutrophils, macrophages, and lymphocytes) that express TNF-α and IL-10 on the 4th and 7th days histologically by immunohistochemical methods. Statistical test results showed that administration of gouramy bone paste in dental pulp decreased TNF-α expression and increased IL-10 expression more than those without gouramy bone paste with a significant difference (p